Associations between influence of infant feeding patterns on the deciduous second molar relationship in preschool-aged children - Hilda Fitria Lubis; Sasha Allayya Tiffany (Majalah Kedokteran Gigi Indonesia, 2019)
Exclusive breastfeeding during the first six months of life is extremely important for the development of the dentocraniofacial structure, occlusion, breathing and swallowing during childhood. The prevalence severity rate of malocclusion in children who were breastfed is lower than those who were bottle-fed. The aim of this study is to evaluate the associations of infant feeding patterns on the deciduous second molar relationship in preschool aged children (3-5 years old children) of selected preschools in and around Medan Selayang. This study used analytic cross-sectional study design as the research method. The sampling was carried out by purposive sampling technique. This study involved  130 children aged 3-5 years as the sample, who consisted of two groups, the exclusively breastfed group and the bottle-fed group with the inclusion criteria of the children having a good oral and dental health. The result is statistically analyzed using Chi Square with a significance level of p<0.05. There was a significant difference between children who were breastfed and those who were bottle-fed. Children who were breastfed mostly had mesial step (55, 4%), followed by distal step(27.7%) and flush (16.9%), while those children who were bottle-fed mostly had distal step (46.2%), flush (33.8%), and mesial steps (20%). Based on Chi Square test, it is shown that there is a significant relationship between infant feeding patterns to primary molar relationships (p<0.001).